2002
DOI: 10.1044/0161-1461(2002/008)
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation in Children With Specific Language Impairment

Abstract: Emotion regulation warrants further research to determine if it is associated with specific social outcomes in children with SLI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
2
13

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(138 citation statements)
references
References 26 publications
3
120
2
13
Order By: Relevance
“…In another study, the children with specific speech impairment are reported to have worse emotion regulation skills than those without. In addition, emotion regulation problems were found to be higher in girls than in boys 18 .…”
Section: Introductionmentioning
confidence: 96%
“…In another study, the children with specific speech impairment are reported to have worse emotion regulation skills than those without. In addition, emotion regulation problems were found to be higher in girls than in boys 18 .…”
Section: Introductionmentioning
confidence: 96%
“…The exemplary work of the National Research Council's (2005) series How Students Learn summarizes research across disciplines to emphasize how specific teaching strategies can enhance young children's learning (Bransford, Brown, & Cocking, 1999). The theoretical foundation for the conceptualization of instructional supports in the CLASS framework comes primarily from research on children's cognitive and language development (e.g., Carver & Klahr, 2001;Catts, Fey, Zhang, & Tomblin, 2001;Fujiki, Brinton, & Clarke, 2002;Romberg, Carpenter, & Dremock, 2005;Taylor, Pearson, Peterson, & Rodriguez, 2003;Vygotsky, 1991;Wharton-McDonald et al, 1998). A student's cognitive and language development is contingent on the opportunities adults provide to express existing skills and scaffold more complex ones (Davis & Miyake, 2004;Skibbe, Behnke, & Justice, 2004;Vygotsky, 1991).…”
Section: Instructional Supportsmentioning
confidence: 99%
“…Finalmente, y siempre en la misma línea argumental, nos encontramos con la propuesta . Los enfoques situados en el medio del continuo incorporan una serie de procedimientos híbridos ya que recurren a técnicas conductistas pero aplicadas en situaciones de discurso conversacional (por ejemplo, la terapia basada en scripts; el uso de la conversación o de la narración para conseguir objetivos lingüísticos 49,50 ). En cualquier caso, hay pocos datos empíricos que hablen de la efectividad y de la eficacia en la intervención global en los TEL y sus implicaciones para su desarrollo emocional, académico y social Sin embargo, a veces la intervención con todo el alumnado dentro del aula no es suficiente para cubrir las necesidades de los TEL 59,60 .…”
Section: La Intervención En Los Telunclassified